2010
DOI: 10.1016/j.psychres.2009.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of acoustic startle magnitude, prepulse inhibition, and startle latency in schizophrenia and control families

Abstract: Prepulse inhibition (PPI) is an acoustic startle paradigm that has been used as an operational measure of sensorimotor gating. Many patients with schizophrenia have impaired PPI, and several lines of evidence suggest that PPI may represent a heritable endophenotype in this disease. We examined startle magnitude and latencies in 40 schizophrenia patients, 58 first-degree relatives of these patients and 100 healthy controls. After removing low-startlers, we investigated PPI and startle habituation in 34 schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 79 publications
7
66
1
1
Order By: Relevance
“…In other words, across all racial (and consequently ethnic) identifications, European and Asian genetic ancestry was associated with individual differences in baseline startle. Previous research has indicated that startle magnitude is highly heritable (Anokhin, Heath, Myers, Ralano, & Wood, 2003; Hasenkamp et al, 2010), and results from the present study support the notion that racial differences may be at least partially genetically influenced. Interestingly, neither European nor Asian genetic ancestry was associated with startle potentiation during the NPU-threat task.…”
Section: Discussionsupporting
confidence: 88%
“…In other words, across all racial (and consequently ethnic) identifications, European and Asian genetic ancestry was associated with individual differences in baseline startle. Previous research has indicated that startle magnitude is highly heritable (Anokhin, Heath, Myers, Ralano, & Wood, 2003; Hasenkamp et al, 2010), and results from the present study support the notion that racial differences may be at least partially genetically influenced. Interestingly, neither European nor Asian genetic ancestry was associated with startle potentiation during the NPU-threat task.…”
Section: Discussionsupporting
confidence: 88%
“…The heritability of PPI in the entire COGS-1 sample was lower at 29% (26), which is likely due to the combined influence of the stronger genetic transmission of genes underlying PPI in the multiply affected families and the apparent lack of genetic transmission in the singleton families on the heritability of this endophenotype. Prior heritability estimates for pulse-alone startle magnitude range from 67% to 70% in schizophrenia families and healthy twins, respectively (29, 30), and show reasonable consistency with the estimates obtained for the entire COGS-1 sample (62%), as well as across the subsets stratified by family history (54–60%). Taken together, these data suggest that variation in startle magnitude may be generally, and highly, heritable in humans, and that the inhibition observed in the prepulse paradigm is of particular relevance to schizophrenia, with a substantial genetic component.…”
Section: Discussionsupporting
confidence: 61%
“…Regarding ASR, inter-individual differences appear to be due to other factors than sex such as, for instance, environmental or genetic variation. For example, ASR heritability has been reported to be in the range of 59-61% [55] and 67% [56]. Nevertheless, previous studies reported conflicting results on the impact of sex on ASR: while some found no difference between men and women [32,[35][36][37] others reported larger startle magnitudes in women at least in some ASR parameters [27,38,39].…”
Section: Discussionmentioning
confidence: 99%